2017
DOI: 10.3758/s13423-017-1318-4
|View full text |Cite
|
Sign up to set email alerts
|

The importance of age-related differences in prospective memory: Evidence from diffusion model analyses

Abstract: Event-based prospective memory (PM) refers to relying on environmental cues to trigger retrieval of a deferred action plan from long-term memory. Considerable research has demonstrated PM declines with increased age. Despite efforts to better characterize the attentional processes that underlie these decrements, the majority of research has relied on measures of central tendency to inform theoretical accounts of PM that may not entirely capture the underlying dynamics involved in allocating attention to intent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
51
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(65 citation statements)
references
References 26 publications
12
51
2
Order By: Relevance
“…Unlike previous models, which did not predict PM accuracy (Heathcote, Loft, & Remington, 2015;Horn & Bayen, 2015;Strickland et al, 2017;Ball & Aschenbrenner, 2017), PMDC quantitatively estimates the extent to which proactive control over ongoing task decisions benefits PM accuracy. For both experiments, we found that conditions with higher ongoing task thresholds (non-focal and PM-important), did have higher PM accuracy as a result of those thresholds.…”
Section: Discussionmentioning
confidence: 82%
See 2 more Smart Citations
“…Unlike previous models, which did not predict PM accuracy (Heathcote, Loft, & Remington, 2015;Horn & Bayen, 2015;Strickland et al, 2017;Ball & Aschenbrenner, 2017), PMDC quantitatively estimates the extent to which proactive control over ongoing task decisions benefits PM accuracy. For both experiments, we found that conditions with higher ongoing task thresholds (non-focal and PM-important), did have higher PM accuracy as a result of those thresholds.…”
Section: Discussionmentioning
confidence: 82%
“…Total RT is determined by accumulation time plus non-decision time. non-PM trials using both the LBA and DDM (Ball & Aschenbrenner, 2017;Heathcote, Loft, & Remington, 2015;Horn & Bayen, 2015;Strickland et al, 2017). The modeling revealed that PM cost is largely due to increases in response threshold, and is not due to changes in ongoing task evidence accumulation.…”
Section: Capacity Sharing and Spontaneous Processesmentioning
confidence: 97%
See 1 more Smart Citation
“…Every evidence accumulation modeling study to date that has compared ongoing task performance between control and PM blocks has found elevated thresholds in the latter (Anderson, Rummel & McDaniel, 2018;Ball & Aschenbrenner, 2017;Heathcote et al, 2015;Horn & Bayen, 2015;Horn et al, 2011Horn et al, , 2013Strickland et al, 2017Strickland et al, , 2018, consistent with proactive control. Further implicating control, Strickland et al (2018) showed that participants increased their ongoing task thresholds further when instructed that the PM task was important.…”
Section: Prospective Memory Decision Controlmentioning
confidence: 93%
“…In these models, evidence is first extracted from the stimuli and then accumulated over time until a decision boundary is reached and a response initiated. Among the many evidence-accumulation models, the DDM is the most widely applied, not only in psychology, but also in economics and neuroscience, accounting for experiments ranging from decision making under time-pressure (Dutilh, Krypotos, & Wagenmakers, 2011;Leite, Ratcliff, Lette, & Ratcliff, 2010;Voss, Rothermund, & Brandtstädter, 2008), prospective memory (Ball & Aschenbrenner, 2018;Horn, Bayen, & Smith, 2011) to cognitive control (Gomez, Ratcliff, & Perea, 2007;Schmitz & Voss, 2012). (2) the separation of the two response boundaries (a), representing response caution; (3) the mean starting point of evidence accumulation (z), representing response bias; and (4) mean non-decision time (T er ), which is the sum of times for stimulus encoding and response execution.…”
Section: Case Study: the Diffusion Decision Modelmentioning
confidence: 99%